THE ADDITION OF CAFFEINE IN EARLE’S BALANCED SALT SOLUTION MEDIA WITH WASHING UP METHOD INCREASE MEMBRANE INTEGRITY AND ACROSOMAL SPERM - Satriyasa, Bagus Komang; Mahendra, Agung Nova (BALI MEDICAL JOURNAL, 2014)
Background: caffeine, a methylxanthine derivate, appears to inhibit phosphodiesterase, thereby inhibiting the break down of cAMP and increasing its concentration inside cell. This study aims to assess the effect of caffeine addition in Earles’s Balanced Salt Solution (EBSS) on the increase in membrane integrity and acrosome reaction of spermatozoa using swim up method Methods: This study was carried out at the Clinic of Sexology and Andrology, Sanglah Public Hospital at Denpasar Bali-Indonesia. This study was an experimental study using the design of pre and post test paired control group design. The samples were sperm specimens of eighteen infertile couple male or volunteers who were infertile with age ranged between 20-40 years old. The samples were divided into two groups: treatment group (caffeine + EBSS) and control group (EBSS). The data were analysed statistically by normality test (Kolmogorov - Smirnov Goodness of Fit Test), Homogeneity test, and Paired Student’s t test. Results: The results showed that the caffeine addition in EBSS medium could increase significantly (p<0.05). The integrity of the sperm membrane obtained were from 81.30 % to 86.60 % and acrosomal reaction from 82.60% to 89.60% evaluated by hypo-osmotic swelling test (HOS). The conclusion of this study is that addition of caffeine in EBSS medium increases significantly membrane integrity and acrosomal reaction of the human sperm.